2016
DOI: 10.1111/cpf.12395
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of aerobic exercise intensity on arterial stiffness after glucose ingestion in young men

Abstract: Arterial stiffness increases after glucose ingestion. Acute low- and moderate-intensity aerobic exercise decreases arterial stiffness. However, the acute effects of 30 min of cycling at low- and moderate-intensity [25% (LE trial) and 65% (ME trial) peak oxygen uptake, respectively] on arterial stiffness at 30, 60 and 120 min of a postexercise glucose ingestion. Ten healthy young men (age, 22·4 ± 0·5 years) performed LE and ME trials on separate days in a randomized controlled crossover fashion. Carotid-femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
(55 reference statements)
3
10
2
Order By: Relevance
“…As arterial compliance is partially dependent on endothelial function (Wilkinson et al 2004), the lack of decrease in CCA compliance in the present study may be explained by previous literature showing no decrease in endothelial function in normal weight children during an OGTT (Dengel et al 2007). Moreover, and different to the present study, adult studies have shown increase in arterial stiffness, assessed as pulse wave velocity, following an OGTT (Baynard et al 2009; Kobayashi et al 2018). Differences in the arterial stiffness assessment method (i.e., CCA compliance and distensibility vs central and peripheral pulse wave velocity), or differences in arterial stiffness due to ageing (Lenard et al 2004), may explain discrepancies between the present study and the adult literature.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…As arterial compliance is partially dependent on endothelial function (Wilkinson et al 2004), the lack of decrease in CCA compliance in the present study may be explained by previous literature showing no decrease in endothelial function in normal weight children during an OGTT (Dengel et al 2007). Moreover, and different to the present study, adult studies have shown increase in arterial stiffness, assessed as pulse wave velocity, following an OGTT (Baynard et al 2009; Kobayashi et al 2018). Differences in the arterial stiffness assessment method (i.e., CCA compliance and distensibility vs central and peripheral pulse wave velocity), or differences in arterial stiffness due to ageing (Lenard et al 2004), may explain discrepancies between the present study and the adult literature.…”
Section: Discussioncontrasting
confidence: 79%
“…This is the first study to investigate the impact of different exercise intensities on BRS following the ingestion of a glucose load, which limits direct comparisons with previous studies. We reasoned that performing exercise before the ingestion of a glucose load would confer vascular protection by blunting possible increase in vascular stiffness following the OGTT, as recently reported in adults (Kobayashi et al 2018). Our results do not support this hypothesis as no differences were observed between conditions (HIIE, MIIE and CON) for the delta changes in arterial compliance.…”
Section: Discussionmentioning
confidence: 94%
“…Contrary to our hypothesis, an oral glucose challenge did not change central or peripheral PWV, despite significant increases in blood glucose and insulin concnetrations. These findings suggest that premenopausal women may experience protection against the acute hyperglycaemiainduced increases in arterial stiffness previously reported in healthy populations (Gordin et al, 2007;Kobayashi et al, 2015Kobayashi et al, , 2018Kobayashi et al, , 2019Mullan et al, 2004).…”
Section: Discussionsupporting
confidence: 69%
“…In contrast to the present findings in young women, some previous research in men and postmenopausal women has reported increases in arterial stiffness with hyperglycaemia (Baynard et al, 2009;Gordin et al, 2007;Huang et al, 2007;Kobayashi et al, 2015Kobayashi et al, , 2018Kobayashi et al, , 2019Mullan et al, 2004). Most directly comparable to the methods of the present study, Kobayashi and colleagues (2015Kobayashi and colleagues ( , 2018Kobayashi and colleagues ( , 2019 found that leg but not aortic (carotid-femoral) PWV increased after acute hyperglycaemia in healthy young men.…”
Section: Impact Of Acute Hyperglycaemia On Pwvsupporting
confidence: 56%
“…Secondly, we did not ask subjects to fast overnight. Previous study showed that arterial stiffness changes happened within 120 min after the ingestion of glucose [11], and there was also another study demonstrating that arterial stiffness did not differ significantly postprandial [15]. We did the baseline measurement in subjects at least 2 h postprandial, hoping the results of the study would be more practical because people do not deliberately exercise after overnight fasting in daily life.…”
Section: Limitationsmentioning
confidence: 95%